Cooperative Handover Algorithm Based on Auxiliary Carrier in LTE-Advanced Relay System - Jihong Zhao; Weiyang He; Hua Qu (Dianxin kexue)
Handover is one of the most important parts in mobility management.In the LTE-Advanced system,more new technologies such as relay and carrier aggregation and so on were introduced,which put forward higher requirements and challenges to the handover mechanism of system.The handover process of the traditional LTE-Advanced system and LTE-Advanced relay system were analyzed,the cooperative handover algorithm based on auxiliary carrier in LTE-Advanced relay system was proposed.This algorithm makes use of the advantages of wide spreading of low-frequency carrier and rich resources of high-frequency carrier,and in conjunction with relay technology and carrier aggregation technology,achieving the purpose of reducing the handover outage probability and improving the throughput of the system.